2022
DOI: 10.3390/nu14142889
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia, Obesity, Sarcopenic Obesity and Risk of Poor Nutritional Status in Polish Community-Dwelling Older People Aged 60 Years and Over

Abstract: Poor nutritional status (PNS) is a modifiable factor determining abnormalities in body composition-sarcopenia, obesity, and sarcopenic obesity (SO). We aimed to assess the prevalence of these conditions and their association with PNS in 211 community-dwelling older adults. Sarcopenia was diagnosed based on the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) recommendations. Obesity was diagnosed with the Percent Body Fat (>42% in women and >30% in men). Subjects fulfilling the criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
2
9
2
Order By: Relevance
“…In Australia, up to 50% of older adults (>65 years) are malnourished or at an increased risk of malnutrition [ 27 ]. A moderate-high risk of malnutrition has also been reported by other studies conducted in different countries [ 28 , 29 , 30 ]. The evidence suggests that those experiencing hip and knee pain are at an increased risk of sarcopenia (a form of malnutrition where the loss of muscle mass occurs) and falls [ 31 , 32 , 33 ].…”
Section: The Nutrition-related Health Of People Experiencing Painsupporting
confidence: 75%
“…In Australia, up to 50% of older adults (>65 years) are malnourished or at an increased risk of malnutrition [ 27 ]. A moderate-high risk of malnutrition has also been reported by other studies conducted in different countries [ 28 , 29 , 30 ]. The evidence suggests that those experiencing hip and knee pain are at an increased risk of sarcopenia (a form of malnutrition where the loss of muscle mass occurs) and falls [ 31 , 32 , 33 ].…”
Section: The Nutrition-related Health Of People Experiencing Painsupporting
confidence: 75%
“…1). Cochran's Q-test showed a statistically significant difference in the prevalence of severe sarcopenia between the three diagnostic instruments (X 2 (2) = 39.31; p < 0.01). Pairwise comparisons showed that the prevalence of severe sarcopenia was significantly higher when using SPPB than with GS (p < 0.01) and TUG (p < 0.01).…”
Section: Severe Sarcopeniamentioning
confidence: 98%
“…Recent estimates suggest that the overall prevalence of sarcopenia in older adults can range from 10.0% [2] to 82.1% [3,4]. In addition, previous studies show that the prevalence of sarcopenia is higher in older women than in older men [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found a global prevalence of SO of 11% (95% CI, 10%-13%) using various definitions, cutoffs, techniques, and population setting . Using the contemporaneous ESPEN/EASO definition, more recent studies have found a prevalence of SO ranging from 7.9% to 23% in clinical and 7.1% to 9.6% in community-dwelling settings …”
Section: Introductionmentioning
confidence: 99%